1993
DOI: 10.1038/clpt.1993.198
|View full text |Cite
|
Sign up to set email alerts
|

Decreased acetylation of isoniazid in chronic renal failure

Abstract: Pharmacokinetic parameters of isoniazid obtained from 37 normal subjects were compared with parameters obtained from 14 patients with chronic renal failure. In the 29 normal rapid acetylators and eight normal slow acetylators, the mean plasma half-life values of isoniazid were 1.54 +/- 0.31 and 3.68 +/- 0.59 hours, respectively. The plasma half-life values of isoniazid in patients with chronic renal failure varied widely from 1.30 to 10.13 hours, but the values were significantly longer than those of normal su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
39
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(47 citation statements)
references
References 3 publications
(4 reference statements)
6
39
0
2
Order By: Relevance
“…Previous studies have shown that CRF was associated with a decrease in acetylation of drugs, implying that phase II enzymes could also be modified in CRF (du Souich and Erill, 1978;Kim et al, 1993). The results of the present study clearly support this hypothesis because we found a decrease in NAT2 expression in CRF animals.…”
Section: Discussionsupporting
confidence: 82%
“…Previous studies have shown that CRF was associated with a decrease in acetylation of drugs, implying that phase II enzymes could also be modified in CRF (du Souich and Erill, 1978;Kim et al, 1993). The results of the present study clearly support this hypothesis because we found a decrease in NAT2 expression in CRF animals.…”
Section: Discussionsupporting
confidence: 82%
“…The reduction CL NR isoniazid was more pronounced in slow acetylators with CRF. Both of these effects were reversed by transplantation [74,75]. These data suggest that with high extraction drugs that also exhibit polymorphic metabolism, poor metabolizers may be at greater risk for adverse effects of CRF on drug metabolism.…”
Section: Clinical Investigations: Effect Of Chronic Renal Failure On mentioning
confidence: 51%
“…For instance, acetylation of isoniazid is decreased as well as the glucuronidation of morphine, p-aminobenzoic acid, and metoclopramide. [123][124][125][126] Only a few studies have investigated the direct effect of uremic toxins on phase II enzymes. By using primary rat hepatocytes, Simard et al 127 showed that exposure of the cells to clinically relevant concentrations of parathyroid hormone resulted in a reduced gene and protein expression of N-acetyltransferase 2.…”
Section: Intracellular Fate Of Uremic Toxinsmentioning
confidence: 99%